80.6k views
3 votes
I'll give 10 to who ever can answer each ​

I'll give 10 to who ever can answer each ​-example-1

1 Answer

1 vote

Answer:

C''(-2, 4)

Explanation:

For C(-5, 4) the first transformation gives you ...

C' = (-5, (1/2)·4) = (-5, 2) . . . . . . x-value unchanged; y-value halved

Then the second transformatin gives you ...

C'' = (-5 +3, 2 +2) = (-2, 4) . . . . x-value increased by 3; y-value increased by 2

So the transformed point appears to be ...

C''(-2, 4)

_____

Comment on poor problem wording

Ordinarily (a, b) ⇒ (c, d) means that b gets transformed to d. When you have b=f(y) and d=g(y), we don't know how to match b with d. We can assume g(y)=g(b), or we can go with b=f(y). In the latter case, we would have d = g(f^-1(b)). That is, we compute y from the value of b, then use that value of y to compute d. The problem statement seems to offer no basis for choosing one or the other except through the implication that the first transformation has an effect on the result overall.

User Pierre Monico
by
4.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.